Zeitschrift für deutsche Philologie (Herausgebertätigkeit von Norbert Otto Eke ab Bd. 123, 2004)

Towards a Scalable and Flexible Simulation and Testing Environment Toolbox for Intelligent Microgrid Control - Bode, Henrik; Heid, Stefan Helmut; Weber, Daniel; Hüllermeier, Eyke; Wallscheid, Oliver (arXiv:2005.04869)
Micro- and smart grids (MSG) play an important role both for integrating renewable energy sources in conventional electricity grids and for providing power supply in remote areas. Modern MSGs are largely driven by power electronic converters due to their high efficiency and flexibility. Nevertheless, controlling MSGs is a challenging task due to highest requirements on energy availability, safety and voltage quality within a wide range of different MSG topologies. This results in a high demand for comprehensive testing of new control concepts during their development phase and comparisons with the state of the art in order to ensure their feasibility. This applies in particular to data-driven control approaches from the field of reinforcement learning (RL), whose stability and operating behavior can hardly be evaluated a priori. Therefore, the OpenModelica Microgrid Gym (OMG) package, an open-source software toolbox for the simulation and control optimization of MSGs, is proposed. It is capable of modeling and simulating arbitrary MSG topologies and offers a Python-based interface for plug & play controller testing. In particular, the standardized OpenAI Gym interface allows for easy RL-based controller integration. Besides the presentation of the OMG toolbox, application examples are highlighted including safe Bayesian optimization for low-level controller tuning.

ProConAR: A Tool Support for Model-based AR Product Configuration - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Mobile shopping apps have been using Augmented Reality (AR) in the last years to place their products in the environment of the customer. While this is possible with atomic 3D objects, there is is still a lack in the runtime conﬁguration of 3D object compositions based on user needs and environmental constraints. For this, we previously developed an approach for model-based AR-assisted product conﬁguration based on the concept of Dynamic Software Product Lines. In this demonstration paper, we present the corresponding tool support ProConAR in the form of a Product Modeler and a Product Conﬁgurator. While the Product Modeler is an Angular web app that splits products (e.g. table) up into atomic parts (e.g. tabletop, table legs, funnier) and saves it within a conﬁguration model, the Product Conﬁgurator is an Android client that uses the conﬁguration model to place diﬀerent product conﬁgurations within the environment of the customer. We show technical details of our ready to use tool-chain ProConAR by describing its implementation and usage as well as pointing out future research directions.
Keywords: Product Configuration; Augmented Reality; Model-based; Tool Support

Every Node for Itself: Fully Distributed Service Coordination - Schneider, Stefan Balthasar; Klenner, Lars Dietrich; Karl, Holger (IEEE International Conference on Network and Service Management (CNSM))
Modern services consist of modular, interconnected components, e.g., microservices forming a service mesh. To dynamically adjust to ever-changing service demands, service components have to be instantiated on nodes across the network. Incoming flows requesting a service then need to be routed through the deployed instances while considering node and link capacities. Ultimately, the goal is to maximize the successfully served flows and Quality of Service (QoS) through online service coordination. Current approaches for service coordination are usually centralized, assuming up-to-date global knowledge and making global decisions for all nodes in the network. Such global knowledge and centralized decisions are not realistic in practical large-scale networks. To solve this problem, we propose two algorithms for fully distributed service coordination. The proposed algorithms can be executed individually at each node in parallel and require only very limited global knowledge. We compare and evaluate both algorithms with a state-of-the-art centralized approach in extensive simulations on a large-scale, real-world network topology. Our results indicate that the two algorithms can compete with centralized approaches in terms of solution quality but require less global knowledge and are magnitudes faster (more than 100x).
Keywords: distributed management; service coordination; network coordination; nfv; softwarization; orchestration

Self-Driving Network and Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Manzoor, Adnan; Qarawlus, Haydar; Schellenberg, Rafael; Karl, Holger; Khalili, Ramin; Hecker, Artur (IEEE International Conference on Network and Service Management (CNSM))
Modern services comprise interconnected components, e.g., microservices in a service mesh, that can scale and run on multiple nodes across the network on demand. To process incoming traffic, service components have to be instantiated and traffic assigned to these instances, taking capacities and changing demands into account. This challenge is usually solved with custom approaches designed by experts. While this typically works well for the considered scenario, the models often rely on unrealistic assumptions or on knowledge that is not available in practice (e.g., a priori knowledge). We propose a novel deep reinforcement learning approach that learns how to best coordinate services and is geared towards realistic assumptions. It interacts with the network and relies on available, possibly delayed monitoring information. Rather than defining a complex model or an algorithm how to achieve an objective, our model-free approach adapts to various objectives and traffic patterns. An agent is trained offline without expert knowledge and then applied online with minimal overhead. Compared to a state-of-the-art heuristic, it significantly improves flow throughput and overall network utility on real-world network topologies and traffic traces. It also learns to optimize different objectives, generalizes to scenarios with unseen, stochastic traffic patterns, and scales to large real-world networks.
Keywords: self-driving networks; self-learning; network coordination; service coordination; reinforcement learning; deep learning; nfv

Augmented and Virtual Reality Object Repository for Rapid Prototyping - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the 8th International Working Conference on Human-Centered Software Engineering (HCSE'20))

Automatic Fairness Testing of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (Proceedings of the 32th IFIP International Conference on Testing Software and Systems (ICTSS))

“On-The-Fly” Calculation of the Vibrational Sum-Frequency Generation Spectrum at the Air-Water Interface - Ojha, Deepak; Kühne, Thomas D. (Molecules)
In the present work, we provide an electronic structure based method for the “on-the-fly” determination of vibrational sum frequency generation (v-SFG) spectra. The predictive power of this scheme is demonstrated at the air-water interface. While the instantaneous fluctuations in dipole moment are obtained using the maximally localized Wannier functions, the fluctuations in polarizability are approximated to be proportional to the second moment of Wannier functions. The spectrum henceforth obtained captures the signatures of hydrogen bond stretching, bending, as well as low-frequency librational modes.

Disordered crystals from first principles II: Transport coefficients - Kühne, Thomas; Heske, Julian Joachim; Prodan, Emil (Annals of Physics)
This is the second part of a project on the foundations of first-principle calculations of the electron transport in crystals at finite temperatures, aiming at a predictive first-principles platform that combines ab-initio molecular dynamics (AIMD) and a finite-temperature Kubo-formula with dissipation for thermally disordered crystalline phases. The latter are encoded in an ergodic dynamical system (Ω,G,dP), where Ω is the configuration space of the atomic degrees of freedom, G is the space group acting on Ω and dP is the ergodic Gibbs measure relative to the G-action. We first demonstrate how to pass from the continuum Kohn–Sham theory to a discrete atomic-orbitals based formalism without breaking the covariance of the physical observables w.r.t. (Ω,G,dP). Then we show how to implement the Kubo-formula, investigate its self-averaging property and derive an optimal finite-volume approximation for it. We also describe a numerical innovation that made possible AIMD simulations with longer orbits and elaborate on the details of our simulations. Lastly, we present numerical results on the transport coefficients of crystal silicon at different temperatures.

Insight from energy decomposition analysis on a hydrogen-bond-mediated mechanism for on-water catalysis - Salem, M. Alaraby; Kühne, Thomas D. (Molecular Physics)

Wann bin ich wer? Peer-Berater*innen im Spannungsverhältnis - Lebock, Sarah (Journal der Schreibberatung)
Peer-Berater*innen nehmen während eines Beratungsgespräches teilweise intuitiv, teilweise bewusst verschiedene Rollen ein. Dieser Artikel soll einen Beitrag zur Reflexion über das Spannungsverhältnis zwischen der Experten- und Prozessberatungsrolle leisten, um die Selbstprofessionalisierung in der Rolleneinnahme zu fördern. Dafür werden auf theoretischer Ebene die konträren Arbeitsweisen beleuchtet, auf denen beide Rollen basieren. Zur Betrachtung von möglichen Einflussfaktoren auf die Rolleneinnahme wird ein selbst entwickeltes Modell präsentiert, welches zum Austausch über diese Faktoren motivieren soll. Zuletzt wird eine praktische Möglichkeit zur gezielten Reflexion über die eigene Rolleneinnahme anhand eines Fragebogens vorgeschlagen.
Keywords: Expertenberatung; Prozessberatung; Rolleneinnahme; Selbstprofessionalisierung

Numerische Simulation von Gravidestillationsapparaten zur Trennung eines binären Ethanol/Wasser-Gemisches - Wende, Marc; Philippi, Kai; Kenig, Eugeny (10. ProcessNet-Jahrestagung und 34. DECHEMA-Jahrestagung der Biotechnologen)

Active Business Model Development Tools: Design Requirements - Szopinski, Daniel (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology (DESRIST))

Exploring design principles for stimuli in business model development tools - Szopinski, Daniel (Proceedings of the 41st International Conference on Information Systems (ICIS))

Methodenentwicklung zum Entfügen von Stahl-Klebverbindungen bei tiefen Temperaturen - Ditter, Jan

Simple Determination of Fast Curing Parameters for Bonded Structures - Ditter, Jan; Aubel, Tobias; Meschut, Gerson (adhesion ADHESIVES + SEALANTS)

Toss a Coin to your Host - How Guests End up Paying for the Cost of Regulatory Policies - Müller, Michelle; Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (Proceedings of the 41th International Conference on Information Systems (ICIS))

Correlating facet orientation, defect-level density and dipole layer formation at the surface of polycrystalline CuInSe2 thin films - Elizabeth, Amala; Conradi, Hauke; K. Sahoo, Sudhir; Kodalle, Tim; A. Kaufmann, Christian; Kühne, Thomas; Mirhosseini, Hossein; Abou-Ras, Daniel; Mönig, Harry (Acta Materialia)
Individual grains of chalcopyrite solar cell absorbers can facet in different crystallographic directions at their surfaces. To gain a deeper understanding of the junction formation in these devices, we correlate variations in the surface facet orientation with the defect electronic properties. We use a combined analytical approach based on scanning tunneling spectroscopy (STS), scanning electron microscopy, and electron back scatter diffraction (EBSD), where we perform these experiments on identical surface areas as small as 2 × 2 µm2 with a lateral resolution well below 50 nm. The topography of the absorber surfaces indicates two main morphological features: micro-faceted, long basalt-like columns and their short nano-faceted terminations. Our STS results reveal that the long columns exhibit spectral signatures typical for the presence of pronounced oxidation-induced surface dipoles in conjunction with an increased density of electronic defect levels. In contrast, the nano-faceted terminations of the basalt-like columns are largely passivated in terms of electronic defect levels within the band gap region. Corresponding crystallographic data based on EBSD experiments show that the surface of the basalt-like columns can be assigned to intrinsically polar facet orientations, while the passivated terminations are assigned to non-polar planes. Ab-initio calculations suggest that the polar surfaces are more prone to oxidation and resulting O-induced defects, in comparison to non-polar planes. Our results emphasize the correlation between morphology, surface facet orientations and surface electronic properties. Furthermore, this work aids in gaining a fundamental understanding of oxidation induced lateral inhomogeneities in view of the p-n junction formation in chalcopyrite thin-film solar cells.
Keywords: Chalcopyrite absorber; Scanning tunneling spectroscopy; Electron backscatter diffraction; Density functional theory; Surface dipole

Research and Consulting in Data-Driven Strategic Product Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Dumitrescu, Roman (Proceedings of The 11th International Multi-Conference on Complexity, Informatics and Cybernetics (IMCIC 2020))

Research and Consulting in Data-Driven Strategic Product Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Dumitrescu, Roman (Journal of Systemics, Cybernetics and Informatics)

Social interactions and asset pricing bubbles - Steiger, Sören; Pelster, Matthias (Journal of Economic Behavior & Organization)

A Discrete and Continuous Study of the Max-Chain-Formation Problem – Slow Down to Speed Up - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Stabilization, Safety, and Security of Distributed Systems - 22nd International Symposium, SSS 2020, Austin, Texas, USA, November 18-21, 2020, Proceedings)
Most existing robot formation problems seek a target formation of a certain minimal and, thus, efficient structure. Examples include the Gathering and the Chain-Formation problem. In this work, we study formation problems that try to reach a maximal structure, supporting for example an efficient coverage in exploration scenarios. A recent example is the NASA Shapeshifter project, which describes how the robots form a relay chain along which gathered data from extraterrestrial cave explorations may be sent to a home base. As a first step towards understanding such maximization tasks, we introduce and study the Max-Chain-Formation problem, where $n$ robots are ordered along a winding, potentially self-intersecting chain and must form a connected, straight line of maximal length connecting its two endpoints. We propose and analyze strategies in a discrete and in a continuous time model. In the discrete case, we give a complete analysis if all robots are initially collinear, showing that the worst-case time to reach an $\varepsilon$-approximation is upper bounded by $\mathcal{O}(n^2 \cdot \log (n/\varepsilon))$ and lower bounded by $\Omega(n^2 \cdot~\log (1/\varepsilon))$. If one endpoint of the chain remains stationary, this result can be extended to the non-collinear case. If both endpoints move, we identify a family of instances whose runtime is unbounded. For the continuous model, we give a strategy with an optimal runtime bound of $\Theta(n)$. Avoiding an unbounded runtime similar to the discrete case relies crucially on a counter-intuitive aspect of the strategy: slowing down the endpoints while all other robots move at full speed. Surprisingly, we can show that a similar trick does not work in the discrete model.

Preservation of Bifurcations of Hamiltonian Boundary Value Problems Under Discretisation - McLachlan, Robert I; Offen, Christian (Foundations of Computational Mathematics)
We show that symplectic integrators preserve bifurcations of Hamiltonian boundary value problems and that nonsymplectic integrators do not. We provide a universal description of the breaking of umbilic bifurcations by nonysmplectic integrators. We discover extra structure induced from certain types of boundary value problems, including classical Dirichlet problems, that is useful to locate bifurcations. Geodesics connecting two points are an example of a Hamiltonian boundary value problem, and we introduce the jet-RATTLE method, a symplectic integrator that easily computes geodesics and their bifurcations. Finally, we study the periodic pitchfork bifurcation, a codimension-1 bifurcation arising in integrable Hamiltonian systems. It is not preserved by either symplectic on nonsymplectic integrators, but in some circumstances symplecticity greatly reduces the error.

Detection of high codimensional bifurcations in variational PDEs - Kreusser, Lisa Maria; McLachlan, Robert I; Offen, Christian (Nonlinearity)

Analysis of Hamiltonian boundary value problems and symplectic integration - Offen, Christian
Ordinary differential equations (ODEs) and partial differential equations (PDEs) arise in most scientific disciplines that make use of mathematical techniques. As exact solutions are in general not computable, numerical methods are used to obtain approximate solutions. In order to draw valid conclusions from numerical computations, it is crucial to understand which qualitative aspects numerical solutions have in common with the exact solution. Symplecticity is a subtle notion that is related to a rich family of geometric properties of Hamiltonian systems. While the effects of preserving symplecticity under discretisation on long-term behaviour of motions is classically well known, in this thesis (a) the role of symplecticity for the bifurcation behaviour of solutions to Hamiltonian boundary value problems is explained. In parameter dependent systems at a bifurcation point the solution set to a boundary value problem changes qualitatively. Bifurcation problems are systematically translated into the framework of classical catastrophe theory. It is proved that existing classification results in catastrophe theory apply to persistent bifurcations of Hamiltonian boundary value problems. Further results for symmetric settings are derived. (b) It is proved that to preserve generic bifurcations under discretisation it is necessary and sufficient to preserve the symplectic structure of the problem. (c) The catastrophe theory framework for Hamiltonian ODEs is extended to PDEs with variational structure. Recognition equations for A-series singularities for functionals on Banach spaces are derived and used in a numerical example to locate high-codimensional bifurcations. (d) The potential of symplectic integration for infinite-dimensional Lie-Poisson systems (Burgers’ equation, KdV, fluid equations, . . . ) using Clebsch variables is analysed. It is shown that the advantages of symplectic integration can outweigh the disadvantages of integrating over a larger phase space introduced by a Clebsch representation. (e) Finally, the preservation of variational structure of symmetric solutions in multisymplectic PDEs by multisymplectic integrators on the example of (phase-rotating) travelling waves in the nonlinear wave equation is discussed.

A Novel Higher-order Weisfeiler-Lehman Graph Convolution - Damke, Clemens; Melnikov, Vitaly; Hüllermeier, Eyke (Proceedings of the 12th Asian Conference on Machine Learning (ACML 2020))
Current GNN architectures use a vertex neighborhood aggregation scheme, which limits their discriminative power to that of the 1-dimensional Weisfeiler-Lehman (WL) graph isomorphism test. Here, we propose a novel graph convolution operator that is based on the 2-dimensional WL test. We formally show that the resulting 2-WL-GNN architecture is more discriminative than existing GNN approaches. This theoretical result is complemented by experimental studies using synthetic and real data. On multiple common graph classification benchmarks, we demonstrate that the proposed model is competitive with state-of-the-art graph kernels and GNNs.
Keywords: graph neural networks; Weisfeiler-Lehman test; cycle detection

Process design for the forming of semi-tubular self-piercing rivets made of high nitrogen steel
The aim to reduce pollutant emission has led to a trend towards lightweight construction in car body development during the last years. As a consequence of the resulting need for multi-material design, mechanical joining technologies become increasingly important. Mechanical joining allows for the combination of dissimilar materials, while thermic joining techniques reach their limits. Self-piercing riveting enables the joining of dissimilar materials by using semi-tubular rivets as mechanical fasteners. The rivet production, however, is costly and time-consuming, as the rivets generally have to be hardened, tempered and coated after forming, in order to achieve an adequate strength and corrosion resistance. A promising approach to improve the efficiency of the rivet manufacturing is the use of high-strength high nitrogen steel as rivet material because these additional process steps would not be necessary anymore. As a result of the comparatively high nitrogen content, such steels have various beneficial properties like higher strength, good ductility and improved corrosion resistance. By cold bulk forming of high nitrogen steels high-strength parts can be manufactured due to the strengthening which is caused by the high strain hardening. However, high tool loads thereby have to be expected and are a major challenge during the production process. Consequently, there is a need for appropriate forming strategies. This paper presents key aspects concerning the process design for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel. The aim is to produce the rivets in several forming stages without intermediate heat treatment between the single stages. Due to the high strain hardening of the material, a two stage forming concept will be investigated. Cup-backward extrusion is chosen as the first process step in order to form the rivet shank without forming the rivet foot. Thus, the strain hardening effects in the area of the rivet foot are minimized and the tool loads during the following process step can be reduced. During the second and final forming stage the detailed geometry of the rivet foot and the rivet head is formed. In this context, the effect of different variations, for example concerning the final geometry of the rivet foot, on the tool load is investigated using multistage numerical analysis. Furthermore, the influence of the process temperature on occurring stresses is analysed. Based on the results of the investigations, an adequate forming strategy and a tool concept for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel are presented.
Keywords: high nitrogen steel; self-piercing riveting; joining by forming; bulk forming; tool design

Optimierung von JMCTest beim Testen von Inter Method Contracts - Mayer, Stefan

Mining Crowdsourcing Problems from Discussion Forums of Workers - Nouri, Zahra; Wachsmuth, Henning; Engels, Gregor (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)

Persuasiveness of News Editorials depending on Ideology and Personality - El Baff, Roxanne; Al-Khatib, Khalid; Stein, Benno; Wachsmuth, Henning (Third Workshop on Computational Modeling of People's Opinions, Personality, and Emotions in Social Media (PEOPLES 2020))

Mobile Medien – Medienpädagogische und technische Grundlagen, Potential für den Deutschunterricht und Beispiele. - Herzig, Bardo; Martin, Alexander; Klar, Tilman-Mathies (Deutsch Digital. Band 1 Theorie (2. Aufl.))

Als Wirtschaftsinformatiker die digitale Transformation in Organisationen gestalten - Kundisch, Dennis; Beverungen, Daniel

Argument from Old Man's View: Assessing Social Bias in Argumentation - Spliethöver, Maximilian; Wachsmuth, Henning (Proceedings of the 7th Workshop on Argument Mining (ArgMining 2020))

Semi-Supervised Cleansing of Web Argument Corpora - Dorsch, Jonas; Wachsmuth, Henning (Proceedings of the 7th Workshop on Argument Mining (ArgMining 2020))

Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren - Otroshi, Mortaza; Meschut, Gerson
Der Karosseriebau ist zunehmend durch die Verwendung unterschiedlicher Werkstoffe in Mischbauweise gekennzeichnet, was zu einem Einsatz von mechanischen Fügeverfahren geführt hat. Hieraus resultieren die Zielsetzungen, die mechanischen Fügeverfahren in ihrer Effizienz und ihren Einsatzbereichen zu erweitern, sowie die Anzahl der Experimente zu reduzieren und Entwicklungszyklen zu verkürzen. Dies erfolgt mit Unterstützung der numerischen Simulation. Neben der Beschreibung des plastischen Verhaltens gilt es auch, das Schädigungsverhalten abzubilden. Der Fügeprozess bzw. die Fügerichtung erfolgt senkrecht zur Blechoberfläche und führt somit zu einem dreidimensionalen Zustand der Fügelemente. Hieraus leitet sich die Herausforderung ab, das Werkstoffversagen in Abhängigkeit der Beanspruchungssituation zu beschreiben. Ein einfacher Ansatz zur Abbildung des Durchdringens ist ein geometrisches Trennkriterium. Ein solches Kriterium basiert i.d.R. auf einem experimentell beobachteten Verhalten und ist somit nicht prognosefähig für Variationen bzgl. Werkzeugkonfigurationen, Blechdicken- und Werkstoffgüten-Kombinationen. In diesem Projekt wird das Schädigungsmodell GISSMO (Generalized Incremental Stress State dependent damage Model) verwendet, um die Entwicklung der duktilen Schädigung zu beschreiben und den Bruchbeginn während des Stanzniet- und Schneidclinchens vorherzusagen. Der Spannungszustand während der Prozesssimulation wird untersucht und die verschiedenen Schädigungsproben werden experimentell erprobt, um die Versagenskurven zu charakterisieren. Die Versagenskurven werden im Schädigungsmodell GISSMO definiert. Um die Genauigkeit des Modells zu gewährleisten, wird die Verifizierung des Modells durch die Simulation von Schädigungsproben mit dem Schädigungsmodell durchgeführt. Zur Validierung des Modells wird die Simulation des Fügeprozesses mit dem Schädigungsmodell durchgeführt und die Ergebnisse von Simulation und Experiment verglichen. Darüber hinaus werden Sensitivitätsanalysen durchgeführt, um die Einflüsse der Fertigungsprozesse, der Lackierung und des Diskretisierungsgrades auf das Schädigungsverhalten des Materials zu identifizieren. Das IGF-Vorhaben „Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren" der Forschungsvereinigung EFB e.V. wurde unter der Fördernummer AiF 19452N über die Arbeitsgemeinschaft industrieller Forschungsvereinigungen (AiF) im Rahmen des Programms zur Förderung der Industriellen Gemeinschaftsforschung (IGF) vom Bundesministerium für Wirtschaft und Energie aufgrund eines Beschlusses des Deutschen Bundestages gefördert. Der Abschlussbericht ist als EFB-Forschungsbericht Nr. 527 erschienen und bei der EFB-Geschäftsstelle und im Buchhandel erhältlich.

Linear damage accumulation of self-pierce riveted joints - Masendorf, Lukas; Wächter, Michael; Horstmann, Stephan; Otroshi, Mortaza; Esderts, Alfons; Meschut, Gerson
Joining technology is regarded as a key technology for reducing energy consumption and CO2 imitation as well as the use of innovative materials and development of new, resource-saving products. Punch riveting is a widely used and established joining process in many sectors. The white and brown goods, electrical engineering, construction and, in particular, the automotive industry are some of the sectors mentioned here. Since the design and assessment of punch rivet components with regard to structural durability can only be carried out experimentally using prototypes due to a lack of experience and calculation concepts, the improvement of this uneconomical and time-consuming procedure is the goal of this contribution. Therefore, a numerical simulation and design method for cyclically loads punched riveted joints shall be introduced. This concept shall be based on the notch strain concept. The following steps are necessary to achieve the goal shown above: Tensile tests on all materials involved in the joint for determination of tensile strength and quasi-static stress-strain curves Estimation of the cyclic material properties from the tensile strength in order to obtain the strain-life curve and the cyclic stress-strain curve Estimation of mean stress sensitivity from the tensile strength to conduct an amplitude transformation for variable amplitude loadings. Execution of a 2D forming simulation of the joining process to determine the geometry and the stresses and degrees of deformation present in the connection Transferring the results of the forming simulation into a static-mechanical load simulation for determining the relation between the external load and the elastic-plastic strain at the critical point Estimation of the service life by means of the damage parameter Wöhler curves calculated from the strain-life curve In order to verify the simulation and calculation method, service life investigations have been carried out on punched riveted components under constant and variable amplitude load. The test results, as well as the workflow through the fatigue assessment and its accuracy in estimation the fatigue life will be shown in this contribution.
Keywords: punch rivet; notch strain conept; structural durability

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (28th Annual European Symposium on Algorithms (ESA 2020))
Let G = (V,E) be an undirected graph on n vertices with non-negative capacities on its edges. The mincut sensitivity problem for the insertion of an edge is defined as follows. Build a compact data structure for G and a given set S ⊆ V of vertices that, on receiving any edge (x,y) ∈ S×S of positive capacity as query input, can efficiently report the set of all pairs from S× S whose mincut value increases upon insertion of the edge (x,y) to G. The only result that exists for this problem is for a single pair of vertices (Picard and Queyranne, Mathematical Programming Study, 13 (1980), 8-16). We present the following results for the single source and the all-pairs versions of this problem. 1) Single source: Given any designated source vertex s, there exists a data structure of size 𝒪(|S|) that can output all those vertices from S whose mincut value to s increases upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(|S|). 2) All-pairs: There exists an 𝒪(|S|²) size data structure that can output all those pairs of vertices from S× S whose mincut value gets increased upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(k), where k is the number of pairs of vertices whose mincut increases. For both these versions, we also address the problem of reporting the values of the mincuts upon insertion of any given edge. To derive our results, we use interesting insights into the nearest and the farthest mincuts for a pair of vertices. In addition, a crucial result, that we establish and use in our data structures, is that there exists a directed acyclic graph of 𝒪(n) size that compactly stores the farthest mincuts from all vertices of V to a designated vertex s in the graph. We believe that this result is of independent interest, especially, because it also complements a previously existing result by Hariharan et al. (STOC 2007) that the nearest mincuts from all vertices of V to s is a laminar family, and hence, can be stored compactly in a tree of 𝒪(n) size.
Keywords: Mincut; Sensitivity; Data Structure

Reinforcement Learning for Virtual Network Embedding in Wireless Sensor Networks - Afifi, Haitham; Karl, Holger (2020 Thirteenth International Workshop on Selected Topics in Mobile and Wireless Computing (STWiMob'2020))
Upcoming sensing applications (acoustic or video) will have high processing requirements not satisfiable by a single node or need input from multiple sources (e.g., speaker localization). Offloading these applications to cloud or mobile edge is an option, but when running in a wireless senor network (WSN), it might entail needlessly high data rate and latency. An alternative is to spread processing inside the WSN, which is particularly attractive if the application comprises individual components. This scenario is typical for applications like acoustic signal processing. Mapping components to nodes can be formulated as wireless version of the NP-hard Virtual Network Embedding (VNE) problem, for which various heuristics exist. We propose a Reinforcement Learning (RL) framework, which relies on Q-Learning and uses either Greedy Epsilon or Epsilon Decay for exploration. We compare both exploration methods to the result of an optimization approach and show empirically that the RL framework achieves good results in terms of network delay within few number of steps.

Overview of Touché 2020: Argument Retrieval - Bondarenko, Alexander; Fröbe, Maik; Beloucif, Meriem; Gienapp, Lukas; Ajjour, Yamen; Panchenko, Alexander; Biemann, Chris; Stein, Benno; Wachsmuth, Henning; Potthast, Martin; Hagen, Matthias (CEUR Workshop Proceedings)

Spannungszustandsabhängige Schädigungsmodellierung zum Halbhohlstanznieten - Otroshi, Mortaza; Meschut, Gerson (Umformtechnik Blech Rohre Profile)

Brief Announcement: Gathering in Linear Time: A Closed Chain of Disoriented & Luminous Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Stabilization, Safety, and Security of Distributed Systems - 22nd International Symposium, SSS 2020, Austin, Texas, USA, November 18-21, 2020, Proceedings)

Hybrid coupled mode modelling of the evanescent excitation of a dielectric tube by semi-guided waves at oblique angles - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optical and Quantum Electronics)
A dielectric step-index optical fiber with tube-like profile is considered, being positioned with a small gap on top of a dielectric slab waveguide. We propose a 2.5-D hybrid analytical/numerical coupled mode model for the evanescent excitation of the tube through semi-guided waves propagating in the slab at oblique angles. The model combines the directional polarized modes supported by the slab with analytic solutions for the TE-, TM-, and orbital-angular-momentum (OAM) modes of the tube-shaped fiber. Implementational details of the scheme are discussed, complemented by finite-element simulations for verification purposes. Our results include configurations with resonant in-fiber excitation of OAM modes with large orbital angular momentum and strong field enhancement.
Keywords: tet_topic_waveguides

Platform-independent Reputation and Qualification System for Crowdwork - Hemsen, Paul; Hesse, Marc; Löken, Nils; Nouri, Zahra (2nd Crowdworking Symposium)

Monocular Depth Estimation via Listwise Ranking using the Plackett-Luce model - Lienen, Julian; Hüllermeier, Eyke (arXiv:2010.13118)
In many real-world applications, the relative depth of objects in an image is crucial for scene understanding, e.g., to calculate occlusions in augmented reality scenes. Predicting depth in monocular images has recently been tackled using machine learning methods, mainly by treating the problem as a regression task. Yet, being interested in an order relation in the first place, ranking methods suggest themselves as a natural alternative to regression, and indeed, ranking approaches leveraging pairwise comparisons as training information ("object A is closer to the camera than B") have shown promising performance on this problem. In this paper, we elaborate on the use of so-called listwise ranking as a generalization of the pairwise approach. Listwise ranking goes beyond pairwise comparisons between objects and considers rankings of arbitrary length as training information. Our approach is based on the Plackett-Luce model, a probability distribution on rankings, which we combine with a state-of-the-art neural network architecture and a sampling strategy to reduce training complexity. An empirical evaluation on benchmark data in a "zero-shot" setting demonstrates the effectiveness of our proposal compared to existing ranking and regression methods.

Plurality Consensus in Hybrid Networks - Yeole, Paresh Kishor

Nonlinear dielectric properties of random paraelectric-dielectric composites - Myroshnychenko, Viktor; Smirnov, Stanislav; Jose, Pious Mathews Mulavarickal; Brosseau, Christian; Förstner, Jens (Acta Materialia)
The challenge of designing new tunable nonlinear dielectric materials with tailored properties has attracted an increasing amount of interest recently. Herein, we study the effective nonlinear dielectric response of a stochastic paraelectric-dielectric composite consisting of equilibrium distributions of circular and partially penetrable disks (or parallel, infinitely long, identical, partially penetrable, circular cylinders) of a dielectric phase randomly dispersed in a continuous matrix of a paraelectric phase. The random microstructures were generated using the Metropolis Monte Carlo algorithm. The evaluation of the effective permittivity and tunability were carried out by employing either a Landau thermodynamic model or its Johnson’s approximation to describe the field-dependent permittivity of the paraelectric phase and solving continuum-electrostatics equations using finite element calculations. We reveal that the percolation threshold in this composite governs the critical behavior of the effective permittivity and tunability. For microstructures below the percolation threshold, our simulations demonstrate a strong nonlinear behaviour of the field-dependent effective permittivity and very high tunability that increases as a function of dielectric phase concentration. Above the percolation threshold, the effective permittivity shows the tendency to linearization and the tunability dramatically drops down. The highly reduced permittivity and extraordinarily high tunability are obtained for the composites with dielectric impenetrable disks at high concentrations, in which the triggering of the percolation transition is avoided. The reported results cast light on distinct nonlinear behaviour of 2D and 3D stochastic composites and can guide the design of novel composites with the controlled morphology and tailored permittivity and tunability.

Increased load bearing capacity of mechanically joined FRP/metal joints using a pin structured auxiliary joining element - Heyser, Per; Sartisson, Vadim; Meschut, Gerson; Droß, Marcel; Dröder, Klaus (Materials Testing)

Essays on Cooperation in Differential Games - Hoof, Simon

Avoidance of liquid metal embrittlement during resistance spot welding by heat input dependent hold time adaption - Böhne, Christoph; Meschut, Gerson; Biegler, Max; Rethmeier, Michael (Science and Technology of Welding and Joining)

Resistance spot welding simulation can determine the critical stress- and strain-conditions leading to liquid metal embrittlement formation - Biegler, Max; Rethmeier, Michael; Böhne, Christoph; Meschut, Gerson (Joining in Car Body Engineering)

Defining and Verifying Durable Opacity: Correctness for Persistent Software Transactional Memory - Bila, Eleni; Doherty, Simon; Dongol, Brijesh; Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Formal Techniques for Distributed Objects, Components, and Systems - 40th IFIP WG 6.1 International Conference, FORTE 2020, Held as Part of the 15th International Federated Conference on Distributed Computing Techniques, DisCoTec 2020, Valletta, Malta, June 15-19, 2020, Proceedings)

Consistency Analysis of AUTOSAR Timing Requirements - Beringer, Steffen; Wehrheim, Heike (Proceedings of the 15th International Conference on Software Technologies, ICSOFT 2020, Lieusaint, Paris, France, July 7-9, 2020)

Verification Artifacts in Cooperative Verification: Survey and Unifying Component Framework - Beyer, Dirk; Wehrheim, Heike (Leveraging Applications of Formal Methods, Verification and Validation: Verification Principles - 9th International Symposium on Leveraging Applications of Formal Methods, ISoLA 2020, Rhodes, Greece, October 20-30, 2020, Proceedings, Part I)

Fundamental Approaches to Software Engineering - 23rd International Conference, FASE 2020, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2020, Dublin, Ireland, April 25-30, 2020, Proceedings

Tests and Proofs - 14th International Conference, TAP@STAF 2020, Bergen, Norway, June 22-23, 2020, Proceedings [postponed]

Testing Monotonicity of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (CoRR)

Mapping postprandial responses sets the scene for targeted dietary advice - Brand-Miller, Jennie; Buyken, Anette (Nature Medicine)

The relationship between differences in students’ computer and information literacy and response times: an analysis of IEA-ICILS data - Heldt, Melanie; Massek, Corinna; Drossel, Kerstin; Eickelmann, Birgit (Large-scale Assessments in Education)
Abstract Background Due to the increasing use of information and communication technology, computer-related skills are important for all students in order to participate in the digital age (Fraillon, J., Ainley, J., Schulz, W., Friedman, T. & Duckworth, D. (2019). Preparing for life in a digital world: IEA International Computer and Information Literacy Study 2018 International Report. Amsterdam: International Association for the Evaluation of Educational Achievement (IEA). Retrieved from https://www.iea.nl/sites/default/files/2019-11/ICILS%202019%20Digital%20final%2004112019.pdf ). Educational systems play a key role in the mediation of these skills (Eickelmann. Second Handbook of Information Technology in Primary and Secondary Education. Cham: Springer, 2018). However, previous studies have shown differences in students’ computer and information literacy (CIL). Although various approaches have been used to explain these differences, process data, such as response times, have never been taken into consideration. Based on data from the IEA-study ICILS 2013 of the Czech Republic, Denmark and Germany, this secondary analysis examines to what extent response times can be used as an explanatory approach for differences in CIL also within different groups of students according to student background characteristics (gender, socioeconomic background and immigrant background). Methods First, two processing profiles using a latent profile analysis (Oberski, D. (2016). Mixture Models: Latent Profile and Latent Class Analysis. In J. Robertson & M. Kaptein (Eds.), Modern Statistical Methods for HCI (pp. 275–287). Switzerland: Springer. 10.1007/978-3-319-26633-6 ) based on response times are determined—a fast and a slow processing profile. To detect how these profiles are related to students’ CIL, also in conjunction with students’ background characteristics (socioeconomic and immigrant background), descriptive statistics are used. Results The results show that in the Czech Republic and Germany, students belonging to the fast processing profile have on average significantly higher CIL than students allocated to the slow processing profile. In Denmark, there are no significant differences. Concerning the student background characteristics in the Czech Republic, there are significant negative time-on-task effects for all groups except for students with an immigrant background and students with a high parental occupational status. There are no significant differences in Denmark. For Germany, a significant negative time-on-task effect can be found among girls. However, the other examined indicators for Germany are ambiguous. Conclusions The results show that process data can be used to explain differences in students’ CIL: In the Czech Republic and Germany, there is a correlation between response times and CIL (significant negative time-on-task effect). Further analysis should also consider other aspects of CIL (e.g. reading literacy). What becomes clear, however, is that when interpreting and explaining differences in competence, data should also be included that relates to the completion process during testing.

Goal Achievement, Subsequent User Effort and the Moderating Role of Goal Difficulty - Gutt, Dominik; von Rechenberg, Tobias; Kundisch, Dennis (Journal of Business Research)

Enhancing social cohesion in PE classes within an intercultural learning program: results of a quasi-experimental intervention study - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Physical Education and Sport Pedagogy)

"Solange dieser Mann gut Deutsch sprechen kann, ist auch kein Problem...": Evaluative Reaktionen auf einen L2-Akzent aus Sicht von Sprecher*innen - Müller, Mareike; Settinieri, Julia (Fremdsprachen Lehren und Lernen)
This article investigates learners’ accounts of and reactions to interlocutors’ evaluations of their L2 pronunciation. Previous studies demonstrate both the pervasiveness of social evaluation processes in native and non-native speaker interactions and the impact of learners’ beliefs about pronunciation on their learning and communicative behavior. Adding to these strands of research, this project sheds light on how learners perceive evaluative reactions to their accents by native speakers and the relationship between such evaluations and learners’ reported evaluative, emotional and behavioral responses. The study draws on 8 international students at a German university. The data were collected in semi-structured interviews and analyzed within the framework of qualitative content analysis. The results give insight into conditions and strategies that may support learners in establishing constructive interpretations of the effects of their accents on their social acceptance.

Systematik zur Digitalisierung von Produktprogrammen - Echterfeld, Julian

Systematik zur integrativen Entwicklung von mechatronischen Produkten und deren Prüfmittel - Lukei, Meinolf

Die Anbahnung einer forschenden Grundhaltung im Praxissemester – eine empirische Analyse von Bedingungen und Entwicklungsverläufen - Homt, Martina

Above 60 GHz Bandwidth 10 GS/s Sampling Rate Track-and-Hold Amplifier in 130 nm SiGe BiCMOS Technology - Wu, Liang; Weizel, Maxim; Scheytt, Christoph (2020 IEEE International Symposium on Circuits and Systems (ISCAS))
This paper presents a broadband track-and-hold amplifier (THA) based on switched-emitter-follower (SEF) topology. The THA exhibits both large- and small-signal bandwidth exeeding 60 GHz. It achieves an effective number of bits (ENOB) of 7 bit at 34 GHz input frequency and an ENOB of >5 bit over the whole input frequency bandwidth at sampling rate of 10 GS/s. Much higher sampling rates are possible but lead to somewhat worse performance. The chip was fabricated in a 130 nm SiGe BiCMOS technology from IHP (SG13G2). It draws 78 mA from a -4.8 V supply voltage, dissipating 375 mW.

Sensitivity Analysis of a Low-Power Wake-Up Receiver Using an RF Barker Code SAW Correlator and a Baseband Narrowband Correlator - Abughannam, Saed; Scheytt, Christoph (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC 2020))
In this paper we propose a novel low-power receiver architecture which uses a direct-detection receiver in combination with a 2.44 GHz 13 bit Barker Code SAW correlator for improvement of co-channel interference. Furthermore, to improve receiver sensitivity, a narrowband baseband correlator which uses pulse position modulation (PPM) is proposed. The receiver can be used as a Wake-up Receiver (WuRx) in Wireless Sensor Networks (WSN) to minimize the power dissipation and provide asynchronous and on-demand data communication. We present a rigorous analysis of the receiver. It shows that the RF front-end (SAW correlator and envelope detector) alone suffers from poor sensitivity due to the high baseband bandwidth and the absence of an RF low noise amplifier. However, by adding the narrowband correlator with an innovative Pulse Position Modulation (PPM) scheme, the overall sensitivity of the receiver reaches -63.1 dB with an improvement of 17.7 dB due to the use of the narrowband correlator that reduces the baseband bandwidth from 50 to 0.84 MHz. By scaling the narrowband correlator bandwidth further down, the receiver sensitivity can be further improved.

A Scalable Platform for QEMU Based Fault Effect Analysis for RISC-V Hardware Architectures - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2020 - Methods and Description Languages for Modelling and Verification of Circuits and Systems; GMM/ITG/GI-Workshop)
Fault effect simulation is a well-established technique for the qualification of robust embedded software and hardware as required by different safety standards. Our article introduces a Virtual Prototype based approach for the fault analysis and fast simulation of a set of automatically generated and target compiled software programs. The approach scales to different RISC-V ISA standard subset configurations and is based on an instruction and hardware register coverage for automatic fault injections of permanent and transient bitflips. The analysis of each software binary evaluates its opcode type and register access coverage including the addressed memory space. Based on this information dedicated sets of fault injected hardware models, i.e., mutants, are generated. The simulation of all mutants conducted with the different binaries finally identifies the cases with a normal termination though executed on a faulty hardware model. They are identified as a subject for further investigations and improvements by the implementation of additional hardware or software safety countermeasures. Our final evaluation results with automatic C code generation, compilation, analysis, and simulation show that QEMU provides an adequate efficient platform, which also scales to more complex scenarios.

Analysis, Design and Implementation of a Fully Integrated Analog Front-End for Microwave RFIDs at 5.8 GHz to be Used with Compact MIMO Readers - Haddadian, Sanaz; Scheytt, Christoph (IEEE Journal of Radio Frequency Identification)
In this paper we present the system and circuit level analysis and feasibility study of applying microwave Radio Frequency Identification (RFID) systems with multipleinput multiple-output (MIMO) reader technology for tracking machining tools in multipath fading conditions of production environments. In the proposed system the MIMO reader interrogates single-antenna tags, and a high RFID frequency of 5.8 GHz is chosen to reduce the size of the reader's antenna array. According to the requirements dictated by the performed system analysis at 5.8 GHz, a low power fully integrated analog frontend (AFE) is designed and fabricated in a standard 65-nm CMOS technology for low power passive transponders. Performance of the Differential Drive Rectifier (DDR) topology as the core of the energy harvesting unit is investigated in detail. A multi-stage DDR power scavenging unit is dimensioned to provide a 1.2 V rectified voltage for 20-30 kQ load range, with a high power conversion efficiency (PCE) for high frequency and low input power level signals. The rectified voltage is then converted to a 1 V regulated voltage for the AFE and the baseband processor with 30 to 50 μW of estimated power consumption. Transistors with standard threshold voltage (VT) have been used for implementation. Measurements of the fabricated multi-stage configuration of the circuit show a maximum PCE of 68.8% at -12.46 dBm, and an input quality factor (Q-factor) of approximately 10. Amplitude-shift keying (ASK) demodulator and backscattering modulator with 80% modulation index, operating according to EPC-C1G2 protocol are applied for data transfer. The AFE consumes less than 1 μW in the reading mode. The AFE tag chip is 0.55 × 0.58 mm 2 .

Design and Fabrication of Barker Coded Surface Acoustic Wave (SAW) Correlator at 2.45 GHz for Low-Power Wake-up Receivers - Ballandras, Sylvain; Abughannam, Saed; Courjon, Emilie; Scheytt, Christoph (GeMiC 2020 - German Microwave Conference)
Low-power receivers use direct-detection receiver architecture for its design simplicity and its low power dissipation. However, the direct-detection based receivers suffer from co-channel interference which significantly degrades the communication reliability. Co-channel interference robustness can be improved by using a BPSK Barker code modulated Surface Acoustic Wave (SAW) correlator as a prior stage to the RF direct detection circuit. This paper reports in details the design, fabrication and measurements of a 2.45 GHz SAW correlator with 13 bits length Barker code. The device is fabricated on Lithium Niobate LiNbO3 substrate and it is composed of an input non-coded Inter Digital Transducers (IDT), a Piezoelectric substrate and an output coded IDT. The device wavelength λ is set to 1.6 μm, considering a phase velocity of the wave equal to 3970 m.s-1. Several configurations of the device were designed and fabricated, particularly varying the aperture and the non-coded IDT length to find out the optimal device configuration. All devices were found to operate with Insertion Loss (IL) ranging from 12 to 15 dB at 2.45 GHz with a tip probing measurement setup, while a packaged sample has an IL of 12.45 dB at 2.44 GHz mounted on a PCB with external 50 Ω LC matching network. Additionally, time-domain measurement for the packaged device shows that the output has a correlation peak with a peak-to-side-lobe (PSL) ratio of 4:1 for a -0.5 dBm input BPSK Barker code signal.

Ein interdisziplinärer und akutmedizinischer Ansatz zur frühestmöglichen Intervention bei Patienten mit Diabetischem Fußsyndrom - Schraeder, Dirk Theodor; Schafran, Tommy; Geisen, Bärbel; Rubbert, Lisa (Orthopädie Technik)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny Y. (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Der richtige Dreh für Simulationen - Schöppner, Volker; Austermeier, Laura; Dietl, Kilian (Blasformen & Extrusionswerkzeuge)
Keywords: Compoundieren; Doppenschneckenextruder; Energieeintrag

SKZ simuliert Doppelschnecke - Schöppner, Volker; Austermeier, Laura; Dietl, Kilian (K Zeitung)
Keywords: Compoundieren; Doppenschneckenextruder; Energieeintrag

DSPG: Decentralized Simultaneous Perturbations Gradient Descent Scheme - Ramaswamy, Arunselvan (2020 28th Euromicro International Conference on Parallel, Distributed and Network-Based Processing (PDP))

Constrained Multi-Agent Optimization with Unbounded Information Delay - Heid, Stefan Helmut; Ramaswamy, Arunselvan; Hüllermeier, Eyke (Proceedings-30. Workshop Computational Intelligence: Berlin, 26.-27. November 2020)

Asynchronous stochastic approximations with asymptotically biased errors and deep multi-agent learning - Ramaswamy, Arunselvan; Bhatnagar, Shalabh; Quevedo, Daniel E (IEEE Transactions on Automatic Control)

Interlaboratory study on rheological properties of cement pastes and reference substances: comparability of measurements performed with different rheometers and measurement geometries - Haist, Michael; Link, Julian; Nicia, David; Leinitz, Sarah; Baumert, Christian; von Bronk, Tabea; Cotardo, Dario; Eslami Pirharati, Mahmoud; Fataei, Shirin; Garrecht, Harald; Gehlen, Christoph; Hauschildt, Inga; et al. (Materials and Structures)
Abstract This paper presents the results of an interlaboratory study of the rheological properties of cement paste and ultrasound gel as reference substance. The goal was to quantify the comparability and reproducibility of measurements of the Bingham parameters yield stress and plastic viscosity when measured on one specific paste composition and one particular ultrasound gel in different laboratories using different rheometers and measurement geometries. The procedures for both in preparing the cement paste and carrying out the rheological measurements on cement paste and ultrasound gel were carefully defined for all of the study’s participants. Different conversion schemes for comparing the results obtained with the different measurement setups are presented here and critically discussed. The procedure proposed in this paper ensured a reasonable comparability of the results with a coefficient of variation for the yield stress of 27% and for the plastic viscosity of 24%, despite the individual measurement series’ having been performed in different labs with different rheometers and measurement geometries.

Stabilization of polyacrylonitrile nanofiber mats obtained by needleless electrospinning using dimethyl sulfoxide as solvent - Moritzer, Elmar; Wortmann, M.; Sabantina, L.; Klocker, M.; Mirasol, JR (JOURNAL OF INDUSTRIAL TEXTILES)

2K-Haftverbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Lochbaum, Ella (Plastverarbeiter)

Additive Manufactured Heat Pipe Injection Mould Element - Moritzer, Elmar; Kartelmeyer, Stephan; Hüttemann, Vincent (Direct Digital Manufacturing Conference 2020)

Additiveteile Direktverschrauben - Moritzer, Elmar; Hillemeyer, Johannes (6. Fachkonferenz 3D-Druck in der Automobielindustrie)

ANALYSIS OF THE ADVANTAGEOUS PROCESS AND MIXING BEHAVIOUR OF WAVE-DISPERSION SCREWS IN SINGLE SCREW EXTRUSION - Schöppner, Volker; Dörner, M.; Marschik, C.

Ansatz zur sicheren Direktverschraubung additiv gefertigter Einschraubtuben - Moritzer, Elmar; Hillemeyer, Johannes (10. Gemeinschaftskolloquium)

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part B. (Superimposed Drag-Pressure Flows in Extrusion) - Schöppner, Volker; Dörner, M.; Marschik, C.; Roland, W.; Schaufler, S.; Steinbichler, G. (Polymers)

CONTEXT OF FIBER LENGTH DISTRIBUTION, HOMOGENEITY AND MECHANICAL PROPERTIES IN DIRECT COMPOUNDING INJECTION MOLDING OF FIBER REINFORCED THERMOPLASTICS - Moritzer, Elmar; Wittke, M. (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

Development of a New Joining Technology for Hybrid Joints of Sheet Metal and Continuous Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Krassmann, Dimitri (73rd Annual Assembly of the International Institute of Welding (IIW))

Development of an Analytical Model to Describe the Disperse Melting in Wave-Dispersion Screws - Schöppner, Volker; Dörner, M.; Marschik, C.; Steinbichler, G. (Polymers)

Die Kunst der Entformung - Moritzer, Elmar; Jilg, J.; Schilp, C.; Krempl, N.; Friesenbichler, W. (Kunststoffe)

EINSATZ VON MASCHINELLEM LERNEN FÜR DIE REZYKLAT-VERARBEITUNG - Moritzer, Elmar; Hopp, Matthias; Wittke, Marius (WAK Jahreszeitschrift)

Entwicklung einer neuartigen Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Krassmann, Dimitri (Joining Plastics)

Entwicklung eines Spritzgießsonderverfahrens zur Herstellung von Hybridbauteilen aus faserverstärkten Thermoplasten und Metallblechen - Moritzer, Elmar; Krassmann, Dimitri; Brikmann, Johannes (10. Fügetechnisches Gemeinschaftskolloquium)

INJECTION MOLD COOLED WITH ADDITIVE MANUFACTURED HEAT PIPE CORE-ELEMENT - Moritzer, Elmar; Kartelmeyer, S.; Hüttemann, M.; Jaroschek, C. (78th Annual Technical Conference for Plastics Professionals (ANTEC))

Inline Surface Activation in the multi Injection Molding Process - Moritzer, Elmar; Mühlhoff, Frederik Marvin (Annual Technical Conference of the Society of Plastics Engineers (ANTEC) 2020)

InMould-Plasma Technologie - Dauerhaft beständige 2K-Verbunde aus originär inkompatiblen Kunststoffen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Lochbaum, Ella; Krampe, Erhard (KGK - Rubberpoint)

An apparatus to synthesize ceramic nanoparticles with a precisely adjusted temperature history and a significant mass output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)

An Apparatus to Synthesize Ceramic Nanoparticles with a Precisely Adjusted Temperature History and a Significant Mass Output - Rasche, David B.; Tigges, Lena; Schmid, Hans-Joachim (Review of Scientific Instruments)
For gas phase nanoparticle production, hot wall reactors are widely used. In this article, we will describe the fundamental design considerations for a hot wall reactor system able to produce oxide nanoparticles. The system is outstanding in its ability to produce mostly spherical nanoparticles at particle sizes of up to 100 nm and even larger at mass outputs in the order of grams per hour by being able to rapidly quench the aerosol. While high production rates or larger particle sizes are already easily obtained with hot wall reactors, it is very challenging to produce these spherical particles at high mass rates. We will show in this research that the temperature and the particle number concentration are the major aspects influencing the particle morphology at the end of the process. Investigation on the performance of the setup shows good control over the temperature and the particle production stability. A representative particle characterization using SEM and scanning mobility particle sizer showed that particles are mostly spherical, while the particle size distribution had a geometric standard deviation close to 1.5. In addition to the aspects mentioned above, a possibility to manipulate the aggregation downstream of the reactor is to be presented as well. We found that applying electrical charges to the aerosol particles (in opposite polarity) can significantly foster aggregation.

Investigation of Plastic Freeformed, Open-Pored Structures with Regard to Producibility, Reproducibility and Liquid Permeability - Moritzer, Elmar; Hirsch, André; Dalmer, C. (Additive Manufacturing in Products and Applications (AMPA))

Kostensenkung beim Mehrkomponenten-Spritzgießen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard (Kunststoff + Verarbeitung)

Mehr Materialkombinationen, weniger Kosten - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (Kunststoffe)

Metallsubstitution durch Spritzgießtechnik gerät allmählich in Reichweite - Moritzer, Elmar; Wittke, M. (MNWP Magazin)